Perspectives on the Technology of Service Operations - Mills, Peter K.; Moberg, Dennis J. (Academy of Management Review, 1982)
Processes and outcomes in manufacturing goods are different from those involved in producing services. These differences necessitate modifications in the theory of sealing off the technical core when applied to the services. Although it is difficult to buffer service operations from customer-induced uncertain ties, it is possible to insulate them from administrative sectors of the organization.